Evaluation of Antimicrobial Effects of Different Concentrations of Triple Antibiotic Paste on Mature Biofilm of Enterococcus faecalis - Mohammad Frough Reyhani; Saeed Rahimi; Zahra Fathi; Sahar Shakouie; Amin Salem Milani; Mohammad Hossein Soroush Barhaghi; Javad Shokri (Tabriz University of Medical Sciences, 2015)
Background and aims. Triple antibiotic paste (TAP) is widely used in endodontics for root canal disinfection, particu-larly in regenerative procedures. The aim of this in vitro study was to evaluate the antimicrobial effects of different concen-trations of TAP at 1-, 2-, 3-, and 4-week intervals on mature Enterococcus faecalis biofilm. Materials and methods. A total of 287 extracted one-rooted human central incisors were infected with E. faecalis ATCC 29212 after removing the crown and preparation. The root canal space was filled with one of the 0.01-, 0.1-, 1-, 10-, 100-, and 1000-mg/mL concentrations of TAP or normal saline (control). The root canal dentin was sampled after 1, 2, 3, and 4 weeks. The dentinal shavings were cultured on Mueller-Hinton agar plates after serial dilutions. The classic colony-forming unit (CFU) counting technique was used to determine remaining bacterial counts. Data were analyzed by using the two-way ANOVA, post hoc Tukey tests and one-way ANOVA (P<0.05). Results. TAP completely eliminated E. faecalisbiofilms at all the intervals at concentrations of 1000, 100, and 10 mg/mL, whereas 1-, 0.1-, and 0.01-mg/mL TAP resulted in significant reduction of CFU means compared with the control group. There were no statistically significant differences between the four time intervals. Conclusion. Use of lower concentrations of TAP at short term could eradicate E. faecalis biofilm and decrease high-concentration side effects.